DIGITAL MARKETING SM ENTERTAINMENT MELALUI SM CULTURE UNIVERSE PROJECT - Soepeni R A H Dikky; Petrus Ana Andung; I Gusti A R Pietriani (LPPM Universitas Adhirajasa Reswara Sanjaya, 2022)
The success of K-pop in the world cannot be separated from the role of companies or private agencies in South Korea, one of which is SM Entertainment. In early 2021, SM announced the release of the SM Culture Universe Project. In the SM Culture Universe project, SM has some original SM content namely Re-Mastering & Re-Masterpiece, SM Classic, iScream, Beyond Live, and AR Technology on some of its products. To market this content/product, SM uses several social media, one of which is Instagram. On the main account @smtown, SM interacts with the public and carries out digital marketing activities on SMCU content. This study aims to map digital-based communication routines between SM Entertainment and fans through the SM Culture Universe Project and map the application of SM Entertainment's Digital Marketing to SM Culture Universe Project content through Instagram social media. This research was studied using the Virtual Ethnography method and analyzed with the theory of Social Constructions Of Technology and using important concepts such as digital media, social media activity, and digital marketing. The results show that the routine communication that occurs is that SM uploads content on Instagram @smtown to convey the SMCU project to the public. Feedback given by the public is in the form of social media activities such as leaving comments, liking, sharing, and so on. The form of digital marketing that SM Entertainment does to SMCU through Instagram @smtown is that SM makes content posts only in outline, while for more detailed information, SM has linked a link that can be connected to the official website www.smentertainment.com, www.smglobalshop.com and youtube, besides that, SM also marked a special Instagram account for SMCU content and album products or merchandise, namely @smtownstation, @screamrecords, @smglobalshop